Sino-orbital Zygomycosis: an atypical presentation of a rare disease in an immunocompetent child - Kumar A., Pragalatha; Kolli, Vinyasa; P., Prem Kumar; G. R., Rajashekar Murthy (International Journal of Contemporary Pediatrics, 2018)
Zygomycosis is a rare life threatening fungal infection in an immunocompromised child. The clinical manifestations of zygomycosis mainly are rhino cerebral, pulmonary, cutaneous, gastrointestinal, and cardiac disease. The diagnosis of zygomycosis is confirmed by direct examinations of clinical specimens and histopathological examination of tissue. The characteristic feature of Zygomycetes in tissue is, the formation of wide, ribbon-like, hyaline, aseptate or sparsely septated hyphae with wide-angle (approximately 90°) branching. The current report describes a case of sino-orbital zygomycosis in a 16-month-old immunocompetent child with atypical presentation. Histopathological examination (HPE) of the tissue confirmed the diagnosis of Zygomycetes.